Prevalence and Risk Factors of Malaria in Iwaka District, Mimika, Papua - Novyan Lusiyana (Acta Medica Indonesiana)
Background: Papua is a high-endemic region for malaria in Indonesia. Malaria transmission is heavily influenced by environmental factors, particularly those related to vector breeding habitats and the homes of infected individuals. Communities in high-endemic areas also exhibit risk behaviors that can increase the likelihood of malaria transmission. Methods: This cross-sectional study was conducted in Iwaka District, Mimika, Papua, and included residents aged 18 years and older who had lived in the district for at least six months and exhibited symptoms of malaria. Subjects with a history of malaria or those under antimalarial treatment in the last two weeks were excluded. We collected demographic characteristics, malaria history, environmental factors, and behavioral components using a structured questionnaire. Each subject underwent a malaria examination using a rapid diagnostic test (RDT). Data were analyzed using STATA software. Results: A total of 863 subjects met the inclusion and exclusion criteria. Of these, 429 (49.7%) were diagnosed with malaria. Malaria cases were predominantly found among males, individuals aged 21– 40 years, those with secondary education, and those working as farmers. Malaria incidence was associated with having family members who had malaria, living near stagnant water, and residing within 100 meters of forests or fields (p < 0.05). The use of bed nets, mosquito repellents, and long-sleeved clothing was low, and most houses had wooden walls without wire mesh protection. Conclusion: Malaria prevalence in Iwaka District is extremely high, with risk factors including age, gender, proximity to stagnant water and forests/fields, and family history of malaria.